Caracterização de Híbridos Simples Experimentais de Milho (Zea Mays L.) - Ferreira, Vitor Guerra [UNESP] (2015)
Being a plant of the Americas, maize cultivation occurs throughout Brazil, and in most regions is carried out in two seasons: first crop or summer crop and second crop. Although the average of grain yield of maize in Brazil is still considered low, technologies such as the development of hybrid cultivars gave the producers a considerable increase of grain yield. However, so that grain yield can continue to evolve gradually, the process of obtaining new cultivars runs continuously by breeders. For maize, the single-cross hybrids are advancing rapidly over other types of hybrid (triple and double) in recognition of its high yield potential in technified crops. The objective of this study was to identify, at the end of the complete process of hybrids formation, those most promising and with agronomic characteristics of a modern hybrid, between 36 single-cross hybrids obtained from brachytic inbred lines and not brachytic inbred lines. The experimental hybrids and six checks were evaluated in a randomized block design with four replications, in Selvíria- MS in four seasons: 2012/13 first crop (season 1), 2012/2013 second crop (season 2), 2013/14 first crop (season 3) and 2013/2014 second crop (season 4). The evaluated traits were days to silking, plant height, ear height, ear length, ear diameter, prolificacy, lodged and broken plants and grain yield. For common hybrids in every season, an analysis of stability and adaptability for grain yield was carried out by the regression method of Heberhart and Rusell. Based on the individual and stability and adaptability analysis, there were identified the following hybrids with potential for evaluations in official testing for both first and second crop: IVF1-6/IVD1-3, 8F/9D, 8F/6D, IVF1- 5/IVD1-8, 5F/9D and 10F/9D. All showed good average for grain yield, stability and responded to the improvement of the environment, of which the first three are early. The ...